Measuring Implicit European and Mediterranean Landscape Identity: A Tool Proposal - Fornara, Ferdinando; Dentale, Francesco; Troffa, Renato; Piras, Simona (Frontiers in Psychology, 2016)
This study presents a tool - the Landscape Identity Implicit Association Test (LI-IAT) - devoted to measure the implicit identification with European and Mediterranean landscapes. To this aim, a series of prototypical landscapes was selected as stimulus, following an accurate multi-step procedure. Participants (N=174), recruited in two Italian cities, performed two LI-IATs devoted to assess their identification with European vs. Not-European and Mediterranean vs. Not-Mediterranean prototypical landscapes. Psychometric properties and criterion validity of these measures were investigated. Two self-report measures, assessing respectively European and Mediterranean place identity and pleasantness of the target landscapes, were also administered. Results showed: (1) an adequate level of internal consistency for both LI-IATs; (2) a higher identification with European and Mediterranean landscapes than respectively with Not-European and Not-Mediterranean ones; and (3) a significant positive relationship between the European and Mediterranean LI-IATs and the corresponding place identity scores, also when pleasantness of landscapes was controlled for. Overall, these findings provide a first evidence supporting the reliability and criterion validity of the European and Mediterranean LI-IATs.